A preliminary experience with a new intramedullary nail for trochanteric fractures - Maniscalco, Pietro; Quattrini, Fabrizio; Ciatti, Corrado; Burgio, Valeria; Rivera, Fabrizio; Di Stefano, Giovanni; Pavone, Vito (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The worldwide incidence of fractures of the proximal end of the femur is increasing as the average age of the population rises. The current surgical gold treatment standard is intramedullary nail fixation. The Authors present their experience with the D-Nail system for intertrochanteric femur fractures. Methods: From January 1st to February 21st 2020 (breakout of COVID-19 pandemic) 34 patients were treated with the D-Nail system: 11 with basicervical fractures, 16 with intertrochanteric stable fractures and 7 with intertrochanteric unstable fractures. In 11 cases, a single cephalic screw was used; in 23 cases, two of them were used. Distal locking was executed in 7 patients. Follow-up time ranged from 2 to 3 months. Results: None of the reported intra- or post-operative complication was linked to the fixation device or the surgical technique. Patients were monitored with clinical and radiological checkups using modified Harris Hip Score to accurately evaluate the fluctuations in the rehabilitation period. Conclusion: The main advantages of this synthesis device are the proximal hole’s peculiar shape, which allows the possibility to position one or two cephalic screws on the same nail, and the silicon coating, which provides numerous biological advantages. Distal locking was executed in selected cases only, based on fracture type. Optimum treatment involves rapid execution of surgery, minimal trauma during surgery, maximum mechanical stability, and rapid weight-bearing. Although our case number is small and follow-up time brief, our results are encouraging.